An evaluation of cesarean rate in turkey by the Robson ten group classification system: How to reduce cesarean rates? - Başer, Emre; Aydoğan Kırmızı, Demet; Özdemirci, Şafak; Kasapoğlu, Taner; Demirdağ, Erhan; Tapısız, Ömer Lütfi; Yalvaç, Ethem Serdar; Moraloğlu Tekin, Özlem (Journal of Surgery and Medicine, 2020)
Aim: Caesarean section (CS) rates, as is the case in the world, showed a significant increase in Turkey over the last decade. The World Health Organization has approved the Robson10-Group Classification System (TGCS) as a global standard to facilitate the analysis and comparison of CS rates. The present study aimed to analyze the TGCS to CS ratio in Turkey and determine CS reduction strategies. Methods: The data for this retrospective cohort study were collected from the records of women who gave birth between January 1, 2011 and December 31, 2014 in a tertiary center. All data were obtained from the hospital database and patient files. The patients were grouped using TGCS. The contribution of each group to CS ratios was determined. Results: Between 2011 and 2014, a total of 25,653 out of 63,476 deliveries were performed by CS. It was determined that the CS rate was 36% in 2011 and increased to 44% in 2014 (P<0.001). According to TGCS, the biggest contribution to this increase belonged to the Class 5 group. This group included 40.7% (2073/5096) of all patients undergoing cesarean section in 2011, 37.3% (2045/5480) in 2012, 27.1% (1859/6857) in 2013, and 36.8% (3025/8220) in 2014. While the rates of patients in Class 1,3 and 10 increased significantly over the years in which the study data were evaluated, rates in Class 2 and 4 decreased (P<0.001). Conclusion: According to TGCS, strategies to prevent the increase in CS ratios should be developed to reduce Class 1, 3 and 5 patients. In this context, strategies to reduce CS ratios can be established through obstetric practices and the health policies of countries.